Transient bilateral vocal cord paralysis after total thyroidectomy - Wongwattana, Panuwat; Wiriyaamornchai, Pannipa (Journal of Medicine and Health Sciences, 2020)
บทคัดย่อ ภาวะสายเสียงเป็นอัมพาตสองข้างหลังการผ่าตัดต่อมไทรอยด์ทั้งหมดเป็นภาวะแทรกซ้อนที่อันตรายถึงชีวิตเนื่องจากมีผลต่อการหายใจ ผู้ป่วยต้องได้รับการรักษาอย่างเร่งด่วน ในบทความนี้แสดงรายงานผู้ป่วยหญิงอายุ 60 ปี มาพบแพทย์ด้วยก้อนขนาดใหญ่ที่ต่อมไทรอยด์ทั้งสองข้างและได้รับการผ่าตัดต่อมไทรอยด์ทั้งหมด หลังผ่าตัดมีภาวะสายเสียงเป็นอัมพาตสองข้าง ผู้ป่วยได้รับการใส่ท่อช่วยหายใจและติดตามประเมินการเคลื่อนไหวของสายเสียงและทางเดินหายใจ พบว่าสายเสียงกลับมาทำงานได้ในวันที่ 7 หลังผ่าตัดและสามารถถอดท่อช่วยหายใจได้โดยไม่ได้รับการเจาะคอ Abstract Bilateral vocal cord paralysis after total thyroidectomy is a life-threatening complication by causing compromised airway. It is an emergency condition that requires immediate treatment.This article reports a 60-year-old woman patient who presented with large thyroid nodules in both thyroid lobes and underwent total thyroidectomy. Postoperatively, the patient had bilateral vocal fold paralysis and was immediately treated with endotracheal intubation. The patient’s airway and vocal fold movement were then serially evaluated. It was found that the vocal fold movement returned at post-op day 7 and the patient can be safely extubated without the requirement of tracheostomy.